Effect of Cold Temperatures on the Viability of Chromobacterium violaceum - Efthimion, Mary H. (1969)
The effect of low, nonfreezing temperatures on the viability of five strains of Chromobacterium violaceum was studied. The viability of cultures grown at 30 C was determined after exposure to various diluents held at 0 to 2 C. A culture diluted at its growth temperature served as the control. Cells of strain N were most sensitive in the early part of the exponential phase of growth. Cells of strains 252 and 341 were most sensitive in the late exponential, early stationary phase of growth. Cells of strain 9 showed greatest loss of viability during the maximal stationary phase. Strain 69 was completely resistant throughout its growth cycle to cold injury. Cell viability was much greater in buffered salts solution than in distilled water, broth, or physiological saline, whether cultures were diluted at room temperature or in the cold. The proportion of cells surviving after exposure to cold, however, was the same regardless of the composition of the diluent. Loss of viability was progressive at 0 to 2 C and reached a maximum after 2 hr. There was no loss of viability of cells exposed to 20 C, but there was some loss at 12 C. Strain 341 cultivated at 15 C was much less sensitive to 0 to 2 C than when it was cultivated at 30 C. The composition of the growth medium seemed to have no effect on the survival of cells exposed to cold. The polyamines, spermine and trimethylenediamine, as well as erythritol and sucrose, exerted some protective action against the effects of cold but not uniformly for all strains studied.